Transition to parenthood and quality of parenting among gay, lesbian and heterosexual couples who conceived through assisted reproduction. Issue 3 (2nd July 2020) - Rubio, Bérengère; Vecho, Olivier; Gross, Martine; van Rijn-van Gelderen, Loes; Bos, Henny; Ellis-Davies, Kate; Winstanley, Alice; Golombok, Susan; Lamb, Michael E.
ABSTRACT: Little research has focused on the emotions felt during pregnancy and early parenthood as well as the initial quality of parenting displayed by first-time parents who conceived using assisted reproduction technologies (surrogacy, donor insemination, and in vitro fertilization). Research on primary and secondary caregivers in gay, lesbian, and heterosexual families is especially sparse. The current study examined 35 gay-father families, 58 lesbian-mother families, and 41 heterosexual-parent families with their infants. Families were assessed at home when their infants were 4 months old (±14 days), and each parent participated in an audio-recorded standardized semi-structured interview in which we explored parental feelings during pregnancy, feelings about the parental role, perceived parental competence, the enjoyment of parenthood, expressed warmth, and emotional over-involvement. Heterosexual parents reported less positive feelings in early pregnancy than lesbian parents, while gay parents reported less positive feelings at the end of pregnancy than lesbian mothers and more positive feelings about parenthood during the first post-partum weeks than heterosexual parents. Family type and caregiver role did not interact to affect reported feelings, perceived competence, enjoyment, warmth, and involvement. The present findings elucidate the transition to parenthood among first-time parents who conceived using assisted reproductive technologies.